Phonemic variations in Hindi speaking aphasics during the immediate post-morbid period - Neena Suri (Journal of All India Institute of Speech and Hearing, 1970)
'If Aphasia is defined first and foremost aa a language disorder then a linguistic analysis of the condition is a priority' (Roman Jakobson 1956).